2013
DOI: 10.1001/jamapediatrics.2013.419
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Screening Strategies for Identifying Pediatric Diabetes Mellitus and Dysglycemia

Abstract: Objective To conduct a cost-effectiveness analysis of screening strategies for identifying children with type 2 diabetes mellitus and dysglycemia (prediabetes/diabetes). Design Cost simulation study. Setting A one-time US screening program. Study Participants A total of 2.5 million children aged 10 to 17 years. Intervention Screening strategies for identifying diabetes and dysglycemia. Main Outcome Measures Effectiveness (proportion of cases identified), total costs (direct and indirect), and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…The ADA acknowledges the limited data supporting A1C for diagnosing type 2 diabetes in children and adolescents. Although A1C is not recommended for diagnosis of diabetes in children with cystic fibrosis or symptoms suggestive of acute onset of type 1 diabetes and only A1C assays without interference are appropriate for children with hemoglobinopathies, the ADA continues to recommend A1C for diagnosis of type 2 diabetes in this cohort (35,36). The modified recommendations of the ADA consensus report "Type 2 Diabetes in Children and Adolescents" are summarized in Table 2.4.…”
Section: Testing For Type 2 Diabetes and Prediabetes In Children And mentioning
confidence: 99%
“…The ADA acknowledges the limited data supporting A1C for diagnosing type 2 diabetes in children and adolescents. Although A1C is not recommended for diagnosis of diabetes in children with cystic fibrosis or symptoms suggestive of acute onset of type 1 diabetes and only A1C assays without interference are appropriate for children with hemoglobinopathies, the ADA continues to recommend A1C for diagnosis of type 2 diabetes in this cohort (35,36). The modified recommendations of the ADA consensus report "Type 2 Diabetes in Children and Adolescents" are summarized in Table 2.4.…”
Section: Testing For Type 2 Diabetes and Prediabetes In Children And mentioning
confidence: 99%
“…As far as we know the different methods have not been compared with respect to cost-effectiveness. Recently Wu et al conducted a costeffectiveness analysis of screening strategies for identifying type 2 diabetes and dysglycaemia (prediabetes) in children and adolescents (aged 10-17 years) [51]. Although they found that the cost of screening per case was high for diabetes, they mentioned that screening for diabetes in youth could be more cost-effective if dysglycaemia was explicitly considered as a screening outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The ADA acknowledges the limited data supporting A1C for diagnosing type 2 diabetes in children and adolescents. Although A1C is not recommended for diagnosis of diabetes in children with cystic fibrosis or symptoms suggestive of acute onset of type 1 diabetes and only A1C assays without interference are appropriate for children with hemoglobinopathies, the ADA continues to recommend A1C for diagnosis of type 2 diabetes in this cohort (44,45). The modified recommendations of the ADA consensus report "Type 2 Diabetes in Children and Adolescents" are summarized in Table 2.5 (46).…”
Section: Screening and Testing For Type 2 Diabetes And Prediabetes Inmentioning
confidence: 99%